Fatty Acid Composition, Antioxidant, and in vitro Anti-inflammatory Activity of Five Cold-Pressed Prunus Seed Oils, and Their Anti-biofilm Effect Against Pathogenic Bacteria - Fratianni, Florinda; d'Acierno, Antonio; Ombra, Maria Neve; Amato, Giuseppe; De Feo, Vincenzo; Ayala-Zavala, Juan Fernando; Coppola, Raffaele; Nazzaro, Filomena (Frontiers in Nutrition, 2021)
Background/Aim: Sweet almond (Prunus amygdalus dulcis) oil is one of the most famous cold-pressed seed oils. However, other species of Prunus can provide oils with healthy properties. We analysed the fatty acid composition, as well as the antioxidant, the in vitro anti-inflammatory properties, and the antibiofilm activity of five commercial vegetable cold-pressed seed oils of apricot, peach, plum, cherry, and black cherry. Methods: Gas Chromatography-Mass Spectrometry performed the analysis of fatty acids (FAs). The antioxidant property of the oils was carried using different tests (2, 2-diphenyl-1-picrylhydrazyl (DPPH assay), Ferric Reducing Antioxidant Power (FRAP), and the 2, 20 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+). The denaturation assay performed on bovine serum albumin was used to evaluate the in vitro anti-inflammatory activity. The anti-biofilm activity was assessed using five pathogenic strains, Acinetobacter baumannii, Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa, and Staphylococcus aureus, through the crystal violet test and the 3-(4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide (MTT), this last used to evaluate the metabolism of the microbial cells present within the biofilm. Results: oleic acid and linoleic acids were the most abundant FAs. Black cherry seed oil exhibited the best antioxidant activity, but in general, the amount of oil need to inhibit at 50% the activity of 1 ml of DPPH assay did not exceed 10 g. The extracts concentration for 50% inhibition the denaturation of the protein (IC50) did not exceed 4.4 g. Linoleic and stearic acids affected the antioxidant activity of the oils; oleic acid, linolenic, and palmitoleic acids exhibited beneficial effects in preserving the BSA denaturation, as resulted by the correlation data. The oils were capable to inhibit the biofilm formation of the pathogens (up to 71.40% of inhibition) as well as acting against their mature biofilm, although with different strength, with values up to 61.54%. Concurrently, they acted also on the pathogen metabolism.